2012
DOI: 10.1016/j.neurobiolaging.2011.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Recovery from ischemia in the middle-aged brain: a nonhuman primate model

Abstract: Studies of recovery from stroke mainly utilize rodent models and focus primarily on young subjects despite the increased prevalence of stroke with age and the fact that recovery of function is more limited in the aged brain. In the present study, a nonhuman primate model of cortical ischemia was developed to allow the comparison of impairments in young and middle-aged monkeys. Animals were pretrained on a fine motor task of the hand and digits and then underwent a surgical procedure to map and lesion the hand-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 102 publications
(175 reference statements)
1
34
0
Order By: Relevance
“…Moreover, other adjacent areas of the frontal and parietal lobes including lateral premotor cortex (LPMC) and posterior parietal cortex (PPC) may also be involved after MCA stroke but the effect of such large lesions on motor recovery has not been a focus of contemporary studies in non-human primates. Indeed, it has been reported that the parietal lobe is the most frequently injured part of the cortical mantle after MCA stroke (Yoo et al, 1998) but injury confined to the precentral motor region continues to be the focus of experimental study(Dancause et al, 2006; Eisner-Janowicz et al, 2008; Moore et al, 2012). Functionally, the anterior and posterior parietal lobe regions are known to play a critical role in processing of somatosensory information for perception (Kaas, 2012) and for control of hand/digit movements for reaching and grasping (Kaas, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, other adjacent areas of the frontal and parietal lobes including lateral premotor cortex (LPMC) and posterior parietal cortex (PPC) may also be involved after MCA stroke but the effect of such large lesions on motor recovery has not been a focus of contemporary studies in non-human primates. Indeed, it has been reported that the parietal lobe is the most frequently injured part of the cortical mantle after MCA stroke (Yoo et al, 1998) but injury confined to the precentral motor region continues to be the focus of experimental study(Dancause et al, 2006; Eisner-Janowicz et al, 2008; Moore et al, 2012). Functionally, the anterior and posterior parietal lobe regions are known to play a critical role in processing of somatosensory information for perception (Kaas, 2012) and for control of hand/digit movements for reaching and grasping (Kaas, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…After ischaemic lesions of the digit region of the primary motor cortex (M1) 75,76 or of the posterior limb of internal capsule 77 , macaques compensate for impairments in precision grip by scooping food rewards with one or more digits towards the palm or proximal thumb. However, these movement strategies can change with task practice, as described below.…”
Section: Compensatory Movement Strategiesmentioning
confidence: 99%
“…However, the risk of stroke is increased as females age [169][170][171][172]. More severe strokes and poorer recovery was observed in elderly women and aged rodents, regardless of the sex [162][163][164][173][174][175][176]. A primary ovarian hormone, estrogen has been associated with the sex difference in ischemic stroke as treatment of estrogen in the male or ovariectomized animals reduced infarct and neuronal death following ischemia [177][178][179][180].…”
Section: Sex-associated Modulation Of Mononuclear Phagocytesmentioning
confidence: 99%